Screening of Significant Variables for Sliced Frying Fish Ball using Plackett–Burman Design - Syamdidi Syamdidi; Theresia Dwi Suryaningrum (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2015)
Screening of significant variables of Sliced Frying Fish Ball (Basreng) has been conducted using Plackett-Burman Design, a statistical method commonly used to reveal the significance of variables in the product development. Four variables were selected namely tapioca flour, potato flour, fish, and frying time. Twelve formulations were peformed and the final products were analyzed for their sensory and texture parameters. Six responses were chosen (appearance, color, odor, taste, texture, overall acceptance and hardness) and then evaluated based on their significance, coefficient value and ranking test through appropriate statistical analysis. The result showed that four variables gave positive and negative effects to the products. Based on overall ranking test, tapioca flour was placed at the first place meaning that it had highest desirable properties followed by frying time, potato flour, and fish flesh. The overall rank test for each ingredient and the attributes provided a reliable data/information to select the most compatible ingredients for further optimization experiment.